The Coordination of Local Translation, Membranous Organelle Trafficking, and Synaptic Plasticity in Neurons - Rajgor, Dipen; Welle, Theresa M.; Smith, Katharine R. (Frontiers in Cell and Developmental Biology, 2021)
Neurons are highly complex polarized cells, displaying an extraordinary degree of spatial compartmentalization. At presynaptic and postsynaptic sites, far from the cell body, local protein synthesis is utilized to continually modify the synaptic proteome, enabling rapid changes in protein production to support synaptic function. Synapses undergo diverse forms of plasticity, resulting in long-term, persistent changes in synapse strength, which are paramount for learning, memory, and cognition. It is now well-established that local translation of numerous synaptic proteins is essential for many forms of synaptic plasticity, and much work has gone into deciphering the strategies that neurons use to regulate activity-dependent protein synthesis. Recent studies have pointed to a coordination of the local mRNA translation required for synaptic plasticity and the trafficking of membranous organelles in neurons. This includes the co-trafficking of RNAs to their site of action using endosome/lysosome “transports,” the regulation of activity-dependent translation at synapses, and the role of mitochondria in fueling synaptic translation. Here, we review our current understanding of these mechanisms that impact local translation during synaptic plasticity, providing an overview of these novel and nuanced regulatory processes involving membranous organelles in neurons.